Smartphone addiction and cross-cultural adjustment among overseas Chinese students: The role of emotion regulation beliefs and strategies - Wanqing, Huang; Fenqing, Liang; Solodukho, Alexander (Frontiers in Psychology, 2022)
Background: Few studies have focused on the cross-cultural adjustment of Chinese students studying in Belarus with the size of this group increasing in recent years. The current study aimed to map the process of cross-cultural adjustment onto various factors including childhood emotional neglect, emotion regulation beliefs, emotional regulation strategies, and smartphone addiction in the international students. Emotional regulation strategy and emotion regulation beliefs could perform as key parts in adapting into overseas life from social learning perspective. Furthermore, smartphone addiction could precipitate a failed adjustment process.Methods: A total of 356 Chinese students in Belarus completed a self-administered questionnaire including the Chinese versions of the 12-item General Health Questionnaire, Sociocultural Adaptation Scale, Mobile Phone Addiction Tendency Scale for College Students, Emotion Regulation Questionnaire, Emotion and Regulation Beliefs Scale, and Childhood Trauma Questionnaire-Short Form. Correlation analysis, regression analysis and t-tests were used to explore the relationship between the variables. Structural equation modelling was carried out to test the hypotheses for association.Results: Emotion regulation beliefs of international students mediated the effect of childhood emotional neglect on cross-cultural adjustment through expression suppression and smartphone addiction. While, in another chain mediation model, childhood emotional neglect affected cross-cultural adjustment only through emotion regulation beliefs and smartphone addiction. Cognitive appraisal independently influenced adjustment through smartphone addiction. Limitations: Limitations include its cross-sectional design and self-reported survey methodology.Conclusions: The importance of emotion regulation beliefs in relation to mobile phone addiction and cross-cultural adjustment, as well as the harmful effects of childhood emotional neglect, should be addressed in the future studies.